(untitled) (Czech Journal of Multidisciplinary Innovations, 2024)
At present, the issue of using radio frequencies in mobile radio communication systems is relevant. This paper presents an analysis and method of efficient use of the radio frequency band in different standards, depending on the type of modulation, using the spectrum of radio frequencies in mobile radio communication systems